Relationship between fine particulate matter (PM2.5) concentration and risk of hospitalization due to chronic obstructive pulmonary disease: a systematic review and meta-analysis - Mouloud Agajani Delavar; Mohammad ali Jahani; Mahdi Sepidarkish; Saeide Alidoost; Hamed Mehdinezhad; Zeynab Farhadi (BMC, 2023)
Abstract Background Short-term exposure to PM2.5 has been associated with human health risks. However, evidence on the association between short-term exposure to PM2.5 and the risk of chronic obstructive pulmonary disease (COPD) remains limited and controversial. This study aimed to specifically assess the relationship between exposure to PM2.5 and the risk of hospitalization due to COPD. Methods A systematic search was conducted in PubMed, Web of Science, and Google Scholar databases from January 1, 2010 to May 1, 2022. The odds ratio (OR) statistic was calculated as a common measure of effect size. Publication bias was also examined in all eligible studies on COPD hospitalization using funnel plots and Egger's test, as well as trim-and-fill method for missing studies on COPD hospitalization. Results A total of 19 studies were included in this meta-analysis. Random-effects models were plotted to calculate the pooled effect size by measuring OR (χ2 = 349.95; df = 18; I2 = 94.86%; P = 0.007; Z = 2.68; P < 0.001). A 10-mg/m3 daily increase in PM2.5 concentration was associated with a 1.6% (95% CI: 0.4-2.9%) increase in COPD hospitalization. There was no publication bias regarding the association between COPD hospitalization and PM2.5 (bias = 1.508; 95% CI: -1.475, 4.491; t = 1.066; P = 0.301). The subgroups of age ≥ 65 years and Asian countries were associated with an increased risk of COPD hospitalization. Besides, higher risks were estimated in the subgroups of studies performed in the warm season, case-crossover studies, studies with three lag days, and studies without adjustments for humidity and temperature confounders, with very small heterogeneity. Conclusion Evidence suggests that short-term exposure to PM2.5 increases COPD hospitalization. Further studies are needed to understand the mechanism of the association between PM2.5 and COPD for reducing air pollution, which can be beneficial for COPD patients.